Philippine flood envelope curves derived from probability distributions of record maxima - Liongson, Leonardo Q. (Philippine Engineering Journal)
The statistical properties of the largest or maximum observation in a series of annual extreme events are described and utilized in order to develop a statistical method for deriving flood envelope curves. The statistical flood envelope method allows for the upward trend of the envelopes due to increasing record length, for regionalization and maximization of statistical parameters, and for transposition of exceptionally high observation. The study aims to reconcile and unify the flood envelope method with the flood frequency method; as a result, both methods are governed by the same limitations. Finally, statistical flood envelope curves for the Philippines are derived based upon the concepts and approaches developed.